PERKULIAHAN BERBASIS PROBLEM SOLVING DENGAN INVESTIGASI KELOMPOK (PBPS-IK) PADA MATERI ANALISIS KUANTITATIF - Pursitasari, Indarini Dwi; Permanasari, Anna; Hendayana, Sumar (Kreatif, 2012)
Abstract: Quantitative analysis subjects requires knowledge and problem solving skills of pre-service chemistry teachers. The aims of this study was to develop and to analyze problem solving skills in quantitative analysis of preservice teachers through Problem Solving Based Lecture with Group Investigation (PSBL-GI). The study was quasy experiment conducted to pre-service teachers of year 2010 in semester three of Chemistry Education programs in one of LPTK in Central Sulawesi that is one experiment class (PBPS-IK) and one control class (concept and practice approach). Data were then collected on using a test problem solving skills with a reliability coefficient of 0.84. The collected data were analyzed qualitatively and tested the difference between N-gain of problem solvingÂ PSBL-GI class with control class at level of significance is 5%. The results showed PSBL-GI can develop pre-service teachers' problem solving skill with categories medium (0,56).The ability to solve problem of pre-service teacher of PSBL-GI class have is greater than the control class. Problem solving skill of high group is better than medium and low groups. The highest N-gain of indicator of problem solving skill is representation (0.82) and the lowest is identification (0,28) while the highest sub subject of quantitative analysis is neutralization titration (0,67) and the lowest is complexometry titration (0,34). Abstrak: Penguasaan materi analisis kuantitatif tidak terlepas dari pengetahuan dan kemampuan problem solving calon guru. Kemampuan problem solving tidak muncul begitu saja namun memerlukan latihan. Tujuan dari penelitian ini adalah mengembangkan dan menganalisis kemampuan problem solving calon guru dalam analisis kuantitatif melalui PBPS-IK. Penelitian dengan quasi experiments ini dilakukan terhadap calon guru angkatan tahun 2010 semester 3 program studi Pendidikan Kimia di salah satu LPTK di Sulawesi Tengah meliputi satu kelas eksperimen (PBPS-IK) dan satu kelas kontrolÂ (strategi ceramah dan latihan soal). Data dikumpulkan menggunakan tes kemampuan problem solving dengan koefisien reliabilitas sebesar 0,84. Data yang terkumpul dianalisis secara kualitatif dan uji perbedaan antara capaian kemampuan problem solving kelas PBPS-IK dengan kelas kontrol pada taraf signifikansi 5 %. Hasil penelitian menunjukkan PBPS-IK dapat mengembangkan kemampuan problem solving calon guru dengan kategori sedang. Calon guru kelas PBPS-IK memiliki kemampuan problem solving yang lebih besar dibandingkan kelas kontrol. Kelompok tinggi memiliki kemampuan problem solving yang lebih baik daripada kelompok sedang dan rendah. Capaian indikator problem solving yang tertinggi adalah representasi (0,82) dan terendah identifikasi (0,28). Sub materi dengan capaian kemampuan problem solving tertinggi adalah titrasi netralisasi (0,67) dan terendah titrasi kompleksometri (0,34). Kata-kata kunci: problem solving, analisis kuantitatif, investigasi kelompok, calon guru